PENGARUH KONSERVATISME AKUNTANSI DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2017) - Warislan, Putri; Putra, Wirmi Eka; Tiswiyanti, Wiwik (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2018)
This research was aimed to know the influence of conservatism accounting and corporate socialresponsibility (CSR) disclosure on earnings management. Variable of conservatism accountingwas proxied by accrual. Variable of corporate social responsibility (CSR) disclosure was proxiedby corporate social responsibility index (CSRI) which refers to guidelines corporate socialresponsibility index (CSRI) version GRI-G4 and GRI Standard. Sample used in this research wasmining companies listed in IDX (Indonesian Stock Exchange) from 2015 – 2017. Samplingtechnique used in this research was purposive sampling. Samples collected in this research were31 companies, a total of 93 data. Data analysis used in this research was descriptive statistics anddata panel regression analysis. Software used to run data was evies 7. The results of this researchshowd as follow. Simultaneously, conservatism accounting and coporate social responsibility(CSR) disclosure had influence on earnings management. Partially, conservatism accounting hadinfluence on earnings management, while corporate social responsibility (CSR) disclosure had noinfluence on earnings management.